Designing an Innovative Curriculum to Improve Participant Competence - Ahmad Muzaki; Koko Adya Winata; Muhammad Nurul Huda; Cepi Hadikusumah (Journal of Multidisciplinary Research, 2026)
Changes in social order and technological advances demand curriculum reform that can develop student competencies in a more contextual and sustainable manner. This article examines the basic principles and strategic approaches to designing an innovative curriculum through a literature review of various contemporary studies in the fields of curriculum and pedagogy. The study's findings indicate that the main characteristics of an innovative curriculum are reflected in design flexibility, strengthening 21st-century competencies, implementing differentiated learning, and utilizing digital technology as an instrument to deepen learning processes and outcomes. Furthermore, elements of sustainability, alignment with actual needs, and data-driven evaluation mechanisms are essential foundations for a curriculum that can adapt to student development and societal changes. This study emphasizes that curriculum innovation is not limited to updating materials but rather creates an adaptive, progressive, and future-oriented educational ecosystem.